Nilai Sosial dalam Novel Canai Karya Panji Sukma (Kajian Sosiologi Sastra) - Septina, Gista; Setiawan, Heru; Munifah, Siti (STKIP PGRI Ponorogo Press, 2024)
The literary work serves as a portrait of societal life, playing a crucial role in prompting individuals to contemplate the values and meanings of life. Novel Canai by Panji Sukma narrates the journey of a father during his youth, facing various social issues such as protests and demonstrations in support of the underprivileged against a corrupt regime. The present research aims to describe the social values depicted in Canai by Panji Sukma, utilizing a qualitative descriptive method with a literature review technique. The study draws data from the novel Canai, employing literature review methods and analyzed through Miles and Huberman’s techniques, including data collection, data reduction, data presentation, and conclusion drawing. The findings illustrate various social values within the novel, including compassion (dedication, familial bonds, loyalty, compassion), responsibility (ownership, empathy), and harmonious living values (justice, tolerance, cooperation, democracy). These social values function as guiding principles, unifying factors, protective shields, and motivators in society.